Coronary risk reduction intervention for siblings and offspring of patients with premature coronary heart disease: the CRISO study protocol for a randomised controlled pilot study - Justin Lee Mifsud; John Stephenson; Felicity Astin; Joseph Galea (Pilot and Feasibility Studies, 2021)
Abstract Background Research has consistently demonstrated that preventive cardiology programs have limited success, and healthy practices among high-risk individuals remain suboptimal. Furthermore, there are no current programmes in Malta that offer support to first-degree relatives of patients with premature coronary heart disease. This internal pilot study will determine the feasibility, acceptability, and potential effectiveness of a preventative intervention. Methods/design We are conducting a 12-month single-centre, two-armed group randomised controlled trial (RCT), recruiting a sample of 100 asymptomatic first-degree relatives of patients with premature coronary heart disease (CHD). The study seeks to test an evidence-based intervention to reduce modifiable risk and determine its feasibility and acceptability. The Intervention will be delivered at an outpatient office based in a large acute academic hospital. It will comprise risk communication using an online risk calculator, a counselling style adapted from motivational interviewing, and 12 weekly telephone goal reinforcement calls (3 months). Control subjects will receive verbal lifestyle advice only. Feasibility will be assessed through recruitment and retention. Qualitative evaluation interviews will be conducted with a subsample of 24 purposefully selected participants at 12 months. Assessment for risk factor changes will be measured at pre-intervention and 6 and 12 months. Associations between variables will also be assessed descriptively. Discussion Preventive cardiology guidelines highlighted the importance of lifestyle interventions, and lifestyle intervention adherence was proven to reduce atherosclerotic cardiovascular disease (ASCVD) risk, regardless of the individual's genetic risk. Preventive cardiology programmes may fail to adequately support persons in modifying risky behaviours, and research demonstrates that healthy practices among high-risk individuals can remain suboptimal. Siblings and offspring of patients with premature CHD are at increased risk of ASCVD. Despite this, there is no process in place for routine screening and support to modify risk. It is hypothesised that participants assigned to the intervention arm will show more cardio-protective lifestyle-related improvement from the baseline than those in the control group. To date, this is the first trial being conducted amongst Maltese first-degree relatives. This study addresses the needed research, and the results will inform a definitive trial. The funding institution is the University of Malta. Trial registration ISRCTN, ISRCTN21559170 ; Registered 06/08/2020,